MSC 2021 Virtual E-Abstract: E-Poster Presentation-Clinical 04 - Stroke Conference, Malaysian (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
1. Extended Hours Thrombolysis Guided By DWI-FLAIR Mismatch. 2. Carotid Artery Stenting For Radiation Induced Late Carotid Stenosis: A Case Report. 3. Cerebral Venous Sinus Thrombosis In Male Gender: A Case Series. 4. Effects Of Malaysian Movement Control Order (MCO) 1.0 Following Covid-19 Pandemic On Acute Stroke Service In Seberang Jaya Hospital. 5. A Rare Pontine Infarct With Abducens Nerve Palsy, Hyperacusis And Contralateral Hemianaesthesia Mimicking Gasperini Syndrome. 6. A Case Report On A Rare Syndrome: Gerstmann Tetrad In A Stroke Patient. 7. Oxford Cognitive Screen Malay Version: Validation Of Stroke-Specific Cognitive Screening Test Pilot Study.